Limiting Factors in Walking Performance of Subjects With COPD. - Sanseverino, Marcela Alves; Pecchiari, Matteo; Bona, Renata Luisa; Berton, Danilo Cortozi; de Queiroz, Francisco Busolli; Gruet, Mathieu; Peyré-Tartaruga, Leonardo A. (Respiratory Care, 2018)
INTRODUCTION: Exercise intolerance is the most predominant symptom in patients with COPD. Nevertheless, it is unclear whether walking economy and gait variability are altered in these patients. Thus, our main objective was to compare the cost of transport and gait variability as a function of speed, including the self-selected walking speed, in subjects with COPD relative to healthy subjects. METHODS: 22 subjects, 11 with COPD (FEV1 = 45 ± 17% of predicted) and 11 age- and sex-matched healthy subjects undertook an evaluation that involved walking on a treadmill at 6 speeds (at 3.2 km/h, at a self-selected walking speed, and at 2 speeds below and 2 speeds above the self-selected walking speed) and measuring the cost of transport (the oxygen consumption normalized by mass and distance), gait variability, perceived dyspnea, and leg fatigue. RESULTS: In subjects with COPD, the cost of transport decreased with increasing walking speed, contrary to healthy subjects, who presented a minimum at the self-selected walking speed. No difference was found in cost of transport between the experimental groups at the same absolute velocity (P = .62). In subjects with COPD, dyspnea sensation rose above the self-selected walking speed, doubling at the maximal walking velocity (P=.03), and gait variability was higher at low speeds. CONCLUSION: Subjects with COPD choose their walking speed so as to keep the dyspnea sensation tolerable and to keep gait variability and cost of transport at an acceptable level. These outcomes suggest that interventions acting on dyspnea and gait pattern may increase patients' self-selected walking speed and improve their quality of life.